“Are Private Equity-backed Public-to-Private transactions outperforming similar public corporations during the current financial crisis?" - jutier, thibaut (2012)
This dissertation is a study of the performance of Public-to-private leveraged buy-outs during the recent period of recession. With the recent degradation of the UK economy, we can rightly assume that these types of highly leverage transactions have been enduring issues to service their substantial debt. Therefore, we suppose they have suffered from liquidity and solvency problems and thus underperformed comparable companies remained public in terms of profitability, efficiency and growth. Following the approaches of recent papers on Leveraged buy-outs, we compare the adjusted performance of this specific form of leveraged buy-outs to the performance of similar transactions conducted in the early 2000s and the performance of comparable public companies. The positive contribution of private equity firms to the performance of these highly leveraged transactions is also under study.